Fulfillment Of Education And Skills For Children In Care - Dimas Al Hakim; Mitro Subroto (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem Children in conflict with the law often face multiple challenges, including social stigma, discrimination, and limited access to education and skills training. These barriers hinder their ability to reintegrate into society after completing their rehabilitation process. Education and vocational training are critical components in ensuring the successful rehabilitation of assisted children, as they provide them with opportunities for personal development, employment, and social reintegration. However, in many rehabilitation centers, educational programs remain inadequate, either due to a lack of resources, trained educators, or appropriate curriculum tailored to the specific needs of these children. Purpose/Study Objectives This research aims to analyze the fulfillment of education and skills development for assisted children within rehabilitation institutions. Specifically, it seeks to identify the challenges that hinder children in conflict with the law from accessing quality education and vocational training, examine the role of social support from families, rehabilitation institutions, and the broader community in motivating and assisting these children, evaluate the effectiveness of current educational programs, and propose recommendations for more inclusive and relevant educational initiatives that align with the needs of assisted children. Design/Methodology/Approach This research utilizes a qualitative approach, which is appropriate for exploring the experiences and perspectives of assisted children and stakeholders involved in their rehabilitation. The study employs in-depth interviews with assisted children, parents, and rehabilitation officers to gain insights into their experiences, challenges, and perceptions regarding educational programs. Observations were conducted within rehabilitation centers to assess the availability and effectiveness of educational resources, facilities, and teaching methods. Additionally, document analysis was carried out by reviewing reports from rehabilitation institutions, government policies, and non-governmental organizations (NGOs) to understand the existing frameworks and gaps in educational provisions for assisted children. Findings The research findings highlight several key aspects. First, many rehabilitation centers lack sufficient learning materials, qualified teachers, and structured curricula tailored to assisted children's needs, making educational fulfillment challenging. Second, social support plays a crucial role, as encouragement from families, rehabilitation officers, and society positively impacts children's motivation and educational success, while the absence of strong external support often leads to decreased self-confidence and learning persistence. Third, the study emphasizes the need for collaborative efforts, as effective educational programs require partnerships between government agencies, NGOs, and community organizations to provide funding, training, and sustainable learning opportunities. Furthermore, skill-based education proves to be highly beneficial, with practical training in areas such as vocational skills, entrepreneurship, and digital literacy increasing the employability of assisted children post-rehabilitation. Lastly, a well-structured education and training system significantly reduces the risk of recidivism by offering constructive future prospects and preventing re-engagement in criminal activities. Paper Type: Research Article